PUSAT KOMIK DI YOGYAKARTA PENDEKATAN FLOATING SPACE SEBAGAI VISUALISASI KISAH KOMIK WAYANG - , FATHONI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Comics is one of the creative industry products that have a large potential in Indonesia. Comics industry could even develop into other industries, such as animation, movie, book, game, and merchandise. The quality of local artists (cartoonists) even been able to compete internationally and recognized by other countries. Unfortunately, the attention and interest on the local comics by people is still lacking that made local comics still difficult to advance, whereas, at the beginning of its appearance, local comics is very popular in Indonesia, but, as time goes by, local comics began to lose interest. A Comic Center as support facilities is needed to maximize the potential of local comic that can accommodate comic-making activities, printing, publishing, sales, community, and a center of comic learning and research. This Comic Center building use floating space concept as the implementation of Wayang Comics image which contains stories about gods in the sky as the basic design concept. Wayang comics is known as orignal Indonesian comic. As one of the public buildings in Yogyakarta, this building is expected to meet all the needs of the local comics industry and can be an alternative recreation place for people so the local comics will be more widely known.